Exploring knowledge, attitude, practices and barriers toward colorectal cancer screening in the United Arab Emirates: a mixed-methods study - Elbarazi, Iffat; Alam, Zufishan; Alshebli, Mouza; Alsunaidi, Lamia; Al-Bluwi, Ghada S. M.; Faheem, Fayeza; Abdullahi, Aminu S.; Ahmed, Luai A.; Al-Maskari, Fatma (Frontiers in Public Health, 2025)
BackgroundColorectal cancer (CRC) is a major contributor to cancer-related morbidity and mortality worldwide. In the United Arab Emirates (UAE), the CRC screening program was introduced in 2014, and it was expected that the program would face challenges, including low participation and poor adherence. However, there is limited research to document awareness and uptake of colorectal cancer screening among the UAE population.AimThis study aimed to assess the knowledge and behaviors of the adult Emirati population in Al-Ain, UAE, toward CRC screening, along with the barriers affecting uptake.MethodA mixed methods research design was employed. Participants (n = 493) recruited from primary care centers, participated in a face-to-face survey that assessed their knowledge and attitudes toward CRC screening. It was followed by in-depth interviews with the consenting participants (n = 16) to explore factors affecting screening uptake. Quantitative data was analyzed via descriptive statistics with Mann–Whitney U and Kruskal-Wallis ANOVA tests applied to examine knowledge differences across sociodemographic variables. Whereas qualitative data was analyzed via thematic analysis.ResultsLow average knowledge scores (10%) and participation levels (12.3%) for CRC screening were evident among the participantsThe majority of the participants held discouraging attitudes, indicating various barriers toward CRC screening. Identified themes relevant to factors affecting screening uptake included knowledge deficits, the influence of inherent beliefs, and the inadequate role of healthcare providers (HCPs).ConclusionIn order to encourage CRC screening among individuals, policymakers need to invest in community awareness and education campaigns that target primary care physicians and adults from all educational backgrounds.